Incidence of stroke and its association with glycemic control and lifestyle in Japanese patients with type 2 diabetes mellitus: The Fukuoka diabetes registry. (February 2021) - Iwase, Masanori; Komorita, Yuji; Ohkuma, Toshiaki; Fujii, Hiroki; Ide, Hitoshi; Yoshinari, Masahito; Oku, Yutaro; Higashi, Taiki; Nakamura, Udai; Kitazono, Takanari
Abstract: Aims: We prospectively investigated the incidence of stroke and its subtypes, risk factors and prognosis in Japanese patients with type 2 diabetes. Methods: A total of 4, 875 participants with type 2 diabetes (mean age 65.4 years, male 57%, previous stroke 10%) were investigated for the development of stroke for 5 years. Risk factors were evaluated using multivariable adjusted Cox proportional models. Results: The incidence rates per 1, 000 person-years were 6.7 for new-onset stroke (ischemic 5.5, hemorrhagic 1.2) and 22.7 for recurrent stroke (ischemic 18.8, hemorrhagic 3.8), respectively. Ischemic stroke was significantly associated with age, male, reduced regular physical activity, HbA1c, diabetic kidney disease and previous stroke. Lacunar infarction was significantly associated with obesity, reduced regular physical activity, HbA1c and diabetic kidney disease, whereas atherothrombotic stroke was significantly associated with age, reduced intake of dietary fiber, reduced regular physical activity, HbA1c and previous stroke. Recurrent stroke was significantly associated with depressive symptom. Thirty-day and one-year survival was 76% and 64% for hemorrhagic stroke, and 96% and 91% for ischemic stroke, respectively. Conclusions: The current study reemphasized the importance of glycemic control and lifestyle modification such as regular physical exercise for stroke prevention in patients with type 2 diabetes.